2021
DOI: 10.2991/assehr.k.211222.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Needs for the Development of Physical Education Learning Model in Elementary School Based on Traditional Game

Abstract: The aim of this research is to obtain information and data related to the analysis of the need for the development of physical education and health learning model based on traditional game in elementary schools. The population of this study were 50 elementary schools in Buleleng District consisting of 13 private elementary schools and 37 public elementary schools. Determination of the sample is determined randomly and selected proportionally in each elementary school. Each of these schools has heterogeneity, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…PJOK plays an essential role because it allows children to be directly involved in a variety of learning experiences through physical activities, play, and sports that are implemented systematically in elementary schools from grades I to VI using a variety of materials (Yoda et al, 2021;Hidajat & Sujarwo, 2022). One of them is the material for the small ball game rounders, which is taught in grade V at the elementary school level in semester 1 and is included in the scope of basic motion of the small ball game (rounders game) (Irsyada, 2018;Saputri, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…PJOK plays an essential role because it allows children to be directly involved in a variety of learning experiences through physical activities, play, and sports that are implemented systematically in elementary schools from grades I to VI using a variety of materials (Yoda et al, 2021;Hidajat & Sujarwo, 2022). One of them is the material for the small ball game rounders, which is taught in grade V at the elementary school level in semester 1 and is included in the scope of basic motion of the small ball game (rounders game) (Irsyada, 2018;Saputri, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although physical testing instruments already exist, there is still a gap in the development of tools specifically designed for junior karate athletes involved in Kumite. Previous studies (Setiawan et al, 2022;Hardiansyah, 2018;Yoda et al, 2021;Rajagukguk & Putra 2022) have shown that current tools aren't perfect and can't accurately predict how well someone will do in Kumite matches. While some studies offer insights into the physical elements important for Kumite (Yoda et al, 2021), a comprehensive evaluation of physical testing instruments and the identification of critical areas for improvement are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Setiawan et al, 2022;Hardiansyah, 2018;Yoda et al, 2021;Rajagukguk & Putra 2022) have shown that current tools aren't perfect and can't accurately predict how well someone will do in Kumite matches. While some studies offer insights into the physical elements important for Kumite (Yoda et al, 2021), a comprehensive evaluation of physical testing instruments and the identification of critical areas for improvement are still needed. Furthermore, the lack of instruments tailored to the unique needs of junior athletes in Kumite poses a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems that still often occur and are encountered in the learning of physical education, sports, and health (PJOK) are the traditional learning process (Masgumelar & Dwiyogo, 2020;Santoso & Wiyanto, 2021;Messakh et al, 2021;Yoda et al, 2021;Hidayat & Sujarwo, 2022). This can be seen from the learning process that is still carried out classically or in large groups where the learning process is carried out without paying attention to the characteristics of students.…”
Section: Introductionmentioning
confidence: 99%